The morphology and kinematics of the gaseous circumgalactic medium of Milky Way mass galaxies – II. Comparison of IllustrisTNG and Illustris simulation results. Issue 4 (4th May 2019) - Kauffmann, Guinevere; Nelson, Dylan; Borthakur, Sanchayeeta; Heckman, Timothy; Hernquist, Lars; Marinacci, Federico; Pakmor, Rüdiger; Pillepich, Annelisa
ABSTRACT: We have carried out a controlled comparison of the structural and kinematic properties of the circumgalactic medium (CGM) around Milky Way mass galaxies in the Illustris and IllustrisTNG simulations. Very striking differences are found. At z  = 0, gas column density and temperature profiles at large radii (∼100 kpc) correlate strongly with disc gas mass fraction in Illustris, but not in TNG. The neutral gas at large radii is preferentially aligned in the plane of the disc in TNG, whereas it is much more isotropic in Illustris. The vertical coherence scale of the rotationally supported gas in the CGM is linked to the gas mass fraction of the galaxy in Illustris, but not in TNG. A tracer particle analysis allows us to show how these differences can be understood as a consequence of the different subgrid models of feedback in the two simulations. A study of spatially matched galaxies in the two simulations shows that in TNG, feedback by supernovae and active galactic nuclei (AGNs) helps to create an extended smooth reservoir of hot gas at high redshifts, which then cools to form a thin, rotationally supported disc at later times. In Illustris, AGNs dump heat in the form of hot gas bubbles that push diffuse material at large radii out of the halo. The disc is formed by accretion of colder, recycled material, and this results in more vertically extended gas distributions above and below the Galactic plane. We conclude that variations in the structure of gas around Milky Way mass galaxies are a sensitive probe of feedback physics in simulations and are worthy of more observational consideration in future.